2022
DOI: 10.3390/vaccines10020255
|View full text |Cite
|
Sign up to set email alerts
|

Approach of Pregnant Women from Poland and the Ukraine to COVID-19 Vaccination—The Role of Medical Consultation

Abstract: There are many arguments for the safety and efficacy of COVID-19 vaccines in pregnancy. The aim of this study is to describe the level of vaccination acceptance, to find the factors that most influence the decision to vaccinate, and to describe the scale of changes in vaccination acceptance influenced by medical information on the safety, efficacy, and benefits of vaccination among pregnant women. A total of 300 patients completed the questionnaire, including 150 in Poland and 150 in the Ukraine. The level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
9
1
1
Order By: Relevance
“…This frequency is lower compared to the values of 84.1% ( 20 ) and of 80.7% ( 19 ) observed by some of us in the same geographic area among different groups of individuals. However, the proportion was considerably higher than the values reported in several other studies among pregnant women: 13.8% in Germany ( 31 ), 16.7% in Ukraine ( 41 ), 29.5% in France ( 38 ), 29.7% in Switzerland ( 42 ), 37% in Turkey ( 43 ), 43% in the United States ( 11 ), and 60.8% in Thailand ( 44 ). Moreover, the observed finding is consistent with those found in Czechia and in China with respectively, 76.6% ( 45 ) and 77.4% ( 46 ) of pregnant populations willing to receive the vaccine.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This frequency is lower compared to the values of 84.1% ( 20 ) and of 80.7% ( 19 ) observed by some of us in the same geographic area among different groups of individuals. However, the proportion was considerably higher than the values reported in several other studies among pregnant women: 13.8% in Germany ( 31 ), 16.7% in Ukraine ( 41 ), 29.5% in France ( 38 ), 29.7% in Switzerland ( 42 ), 37% in Turkey ( 43 ), 43% in the United States ( 11 ), and 60.8% in Thailand ( 44 ). Moreover, the observed finding is consistent with those found in Czechia and in China with respectively, 76.6% ( 45 ) and 77.4% ( 46 ) of pregnant populations willing to receive the vaccine.…”
Section: Discussioncontrasting
confidence: 60%
“…Not surprisingly, women who did not get the COVID-19 vaccine or did not intend to receive it indicated as major reasons the fears about its side effects and doubts about its efficacy. This fear of adverse events was already observed as a prevalent reason for refusing the COVID-19 vaccination in other studies in Italy ( 15 ) and elsewhere ( 13 , 37 41 ). Among the unvaccinated participants, 71.9% reported their willingness to receive the vaccine.…”
Section: Discussionmentioning
confidence: 52%
“…Previous data show that the recommendation and offer of the influenza vaccine by a healthcare provider are critical for uptake in pregnancy 118. Several studies found that a provider’s recommendation was positively associated with covid-19 vaccination 878998110. A large nationwide prospective study in the US was used to characterize vaccination rates and acceptance during pregnancy in the first six months of vaccine rollout 89.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…Only 16.7% of pregnant women surveyed in Ukraine accepted vaccination before medical consultation, according to a study on SARS-CoV-2 vaccination of pregnant women in Poland and Ukraine. 16 According to the same study, the acceptance rate increased to 46% after the consultation, although it remained much lower than in Poland (72.6%). The conclusions of Janousek’s study on pregnant women accepting immunization reveal that the migrant population is at additional risks due to a lack of proper vaccination protection, as well as due to attitudes that contradict current medical advice.…”
Section: Resultsmentioning
confidence: 88%